THE ERROR ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS IN RESOLVING FLAT STRUCTURE WIDTH QUESTIONS OF BILAH KERIS SENGKELET - Susanto, Arif; Asmari, Januar Budi (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Each culture has its own characteristics, like Yogyakarta. It becomes student city, besides, Yogyakarta is one of culture city with its various culture as the main characteristic. One of the culture's arts which is still alive and survive is keris. Keris is believed as the original product of Indonesian culture which has so many types, like Sengkelet. One of philosophy in mathematics educational world is etnomatematika, means mathematics activities at certain culture. In bilah keris sengkelet, there are several shapes of flat structure that we can count its wide. Thus, the research is aimed to know various error of junior high school student's  and its factor in resolving flat structure width questions of bilah keris sengkelet. The researcher wants to know the errors which is related to the concepts and principles in resolving the questions about flat structure width. The research method used is qualitative descriptive. The research subjects is chose based on student's mistakes in resolving diagnostic test of similarities which is given to the students. The qualitative data collecting technique is through documentary and interview. Data analysis is done in qualitatively. The result of the analysis shows that student's errors are; wrong in interpreting the question's information, fail in understanding the concepts and principles in resolving flat structure width questions of bilah keris sengkelet, and technical errors. Student's errors in finishing the questions about the width of flat structure questions related to the weaknesses in understanding the concepts and principles of flat structure. Student's difficulties factors are the lack of variety of the exercises about flat structure width questions which are relating all concepts that is thought to the students.